(untitled) (Al-Academy, 2023)
The actor has mechanisms that were applied in the performance، as it formed a style in the theatrical form (weird)، and the researcher deliberately studied these mechanisms and divided them into four chapters. The researcher divided it into two sections، the first is the actor’s performance requirements، and the second is the boring performance methods in the directors’ theater، and then the researcher concluded the second chapter with the most important indicators. As for the third chapter، the researcher determined the society of his research and the method of selecting the sample (strange) and analyzing the sample and concluded with the most important results of the sample analysis.